A Legal Reconstruction Model for Village-Owned Enterprises (BUMDES) Governance Based on Minimum Regulatory Standards to Strengthen Village-Owned Enterprises (PADES) In North Sumatra - Muhammad Khoirul Ritonga; Ramlan Ramlan; Surya Perdana (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
Village-Owned Enterprises (BUMDes) are expected to strengthen village revenue (PADes), yet many initiatives in practice are constrained by weak governance design, overlapping roles at the village level, limited transparency, and inconsistent compliance with existing regulations. This article formulates a legal reconstruction model for BUMDes governance through Minimum Regulatory Standards (MRS) as an operational bridge between normative rules and implementation needs in North Sumatra. The objective is to develop a structured and applicable governance framework that improves accountability, reduces conflicts of interest, and supports sustainable PADes generation. This research uses a normative-empirical legal approach by integrating statutory and conceptual analysis with an implementation-oriented assessment of governance problems commonly found in BUMDes management. The proposed model consists of: (i) a village-level check-and-balance design (mandate holder–management–supervision), (ii) core SOP and internal control standards for procurement, cash, receivables, inventory, investment, and risk, (iii) performance indicators and public reporting mechanisms to ensure transparency, and (iv) conflict-of-interest controls through ethics rules, role restrictions, and enforceable internal sanctions. The findings argue that the MRS-based reconstruction model provides a concrete legal-institutional blueprint to standardize governance quality, enhance public trust, and improve PADes performance while remaining adaptable to local capacity differences among villages.